Generation of an induced pluripotent stem cell (iPSC) line (INNDSUi007-A) from a patient with Kennedy disease - Bo Li; Yitong Yang; Yingxin Wang; Didi Shan; Jianing Li; Hongxu Wang; Xiaohan Sun; Yao Tang; Yichang Jiao; Xinbo Ji; Zexin Zhan; Bo Kong; et al. (Stem Cell Research)
Abnormal trinucleotide CAG repeat expansions in exon 1 of the Androgen Receptor (AR) gene has been identified as the cause of Kennedy disease (KD). We generated and characterized a human induced pluripotent stem cell (iPSC) line from peripheral blood mononuclear cells (PBMC) of a patient with genetically confirmed KD. The pluripotency of these iPSCs was verified by the expression of several pluripotency markers at both RNA and protein levels, as well as their capability to differentiate into all three germ layers.